A guide for endometrial cancer cell lines functional assays using the measurements of electronic impedance - Kozak, Joanna (Cytotechnology, 2017)
Endometrial cancer cell lines are critical tools to investigate the molecular mechanism of tumorigenesis using the end point cell-based assay such as proliferation, cytotoxicity, apoptosis, anoikis or migration and invasion. The proper assay optimization and performance is essential for physiologically relevant results interpretation. In this study we use label-free real-time cell analysis platform (xCELLigence) to optimize growing conditions for proliferation and migration experiments of two types of endometrial cancer cell lines HEC-1-B, HEC-1-A, KLE, and Ishikawa. Profiling of cell lines by cell index measurement in proliferation and migration experiments was performed. Our experimental approach allowed us to monitor particular stage of the cell growth, to see the relation between seeding density and dynamic cell growth as well as to choose the optimal serum concentration as chemoattractant in migration experiment. The highest rate of proliferation was shown for Ishikawa cells. The rapid pace of cellular migration was observed in case of KLE and HEC-1-B cells as compared to weak migratory activity of Ishikawa cells. The cell index that reflects the cell status characterized real-time cytological profile of each analyzed cell line. These cell profiles were crucial for better planning the classical end-point assays used in further research.